2014
DOI: 10.15640/jibe.v2n4a9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors that Influence Talent Management Competency of Academics in Malaysian GLC’s and Non- Government Universities

Abstract: The aim of this research is to investigate the nature and extent of talent management related factors on talent management competencyforAcademics in threeMalaysian universities. The study explored the literature and identified a broad theorized model by (Davies & Davies, 2010) further by undertaking a literature review from the extant literature some common factors associated to Talent Management the authors developed indicators and multi-item measures to preliminarily test and propose Davies & Davies model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…In a study done on Malaysian universities by Annakis et al (2014) with a sample size of 166, 80% response rate, the findings revealed that four factors emerged explaining 68.6% of the variation, with KMO value of 0.812, which exceeded the recommended value of 0.6. This is by far the threshold required.…”
Section: Findings Of Studies Done In Higher Education Institutionsmentioning
confidence: 88%
See 1 more Smart Citation
“…In a study done on Malaysian universities by Annakis et al (2014) with a sample size of 166, 80% response rate, the findings revealed that four factors emerged explaining 68.6% of the variation, with KMO value of 0.812, which exceeded the recommended value of 0.6. This is by far the threshold required.…”
Section: Findings Of Studies Done In Higher Education Institutionsmentioning
confidence: 88%
“…Talent management is all about planning, recruiting and developing systematic ways through which employee training and career growth can be enhanced and sustained towards achievement of educational institutional goals (Othman and Sumardi 2009). The reason behind these constraining efforts by an institutional leadership is to ensure that the mission and vision of the institution is realised through applicability and flexibility to address global challenges (Annakis 2014). The excellence of higher education institutions can be observed through rebranding and reshaping the economic transformation of a nation through inventory of new academic programmes, research and facilities that attract internationalisation (Isahak 2007).…”
Section: What Is Talent Management Practices (Tmp)mentioning
confidence: 99%
“…Subsequently, educational excellence is the key to world class branding today, as it is the main source of marketable and suitable academic programmes that can facilitate the attraction and retention of foreign and local students Annakis et al, 2014). It is therefore the onus of university leadership to facilitate talented staff to stay in their institutions and at the same time increase staff's capabilities so as to produce graduates that will meet the requirements of the global market.…”
Section: The Nature Of Universities Practice Towards Talent Managementmentioning
confidence: 99%
“…It is therefore the onus of university leadership to facilitate talented staff to stay in their institutions and at the same time increase staff's capabilities so as to produce graduates that will meet the requirements of the global market. Nonetheless, some universities are lagging behind in this aspect and incapacitated in regard to producing the needed human resources to facilitate the needs of the industries in the field (Annakis et al, 2014…”
Section: The Nature Of Universities Practice Towards Talent Managementmentioning
confidence: 99%
“…The items of the survey tool were from the literature studies carried out by (Annakis et al, 2014;Oehley, 2013). The reliability of the instruments subconstructs for the talent management construct ranged between 0.83,0.79,0.78 and its only one that appeared to be on the margin with 0.71.…”
Section: Measuring Instrumentsmentioning
confidence: 99%